Perspective Taking and Growth at The Workplace: The Mediating Effect of Contingent Reward - Cristian – Liviu VELE (Communications of International Proceedings, 2022)
The present article focuses on the implications of contingent reward, as the dimension of transactional leadership, on employee perspective thinking and growth. In the even more challenging global business environment, characterized by post pandemic problems due to shortages in supply and delays in production, organizations need to find new more efficient ways to adapt and to increase efficiency. The human resource has become nowadays even more crucial in ensuring survival and long term sustainable development and for this reason this study aims at looking into the effects of rewards on the manner in which individuals take into consideration other opinions and base their decision on other views. At the same time, constant individual growth from a professional point of view it's required in order to better adapt the new challenges and in order to be able to find new creative solution to organizational problems. The quantitative research was conducted using a questionnaire based on the Multifactor Leadership Questionnaire (MLQ) which was applied to employees that work in companies located in the northern part of Romania. The answers were statistically analyzed, and the findings led to the conclusion that contingent reward has a positive influence both on perspective thinking and on employee growth. At the same time, it was noticed that perspective thinking has a positive influence on employee growth.
Keywords: transactional leadership; perspective taking; employee development